G40 Shaping the design, methods and ethics of a qualitative study: Consulting with children, young people, parents and a teacher. (24th May 2017) - Snodin, J; Bray, L; Carter, B; Jack, B
Abstract : Aims: This paper will present the patient and public involvement (PPI) activities which informed the development of a qualitative study exploring the perceptions and experiences of children aged 4–12 years with long term conditions of being held for clinical procedures within acute health care settings. Methods: Consultation took place in three steps. A children's advisory group (CAG) was consulted with on 2 occasions, in addition to parents and a primary school teacher known to the researcher. Results: The CAG identified that an intended research objective was unimportant to them. This discovery ensured that the focus of the study reflected the aspects of care which matter most to children. The CAG also reported that data collection tools chosen by the researcher were engaging. This knowledge reassured the researcher that methods utilised would be engaging for children, and be likely to promote participation and positively influence the quality of data gathered. A teacher was able to improve on the research documents to better reflect useful phrasing and the development of literacy among children. Improving the efficacy of the research documents for children reassured the researcher that the documents would appropriately inform assent. Parents reported different understandings of the term 'clinical holding' chosen by the researcher. Identification of a term that had shared meaning for parents is fundamental in promoting informed consent. The CAG reported different understandings of terms chosen by the researcher. Identification of terms which had shared meaning for children is fundamental in promoting the degree to which assent can be informed. Conclusion: Obligations of researchers to engage with PPI consultation is a comparatively new aspect to research activity, and there is a risk that consultation processes are viewed as a tick box exercise in order to meet the requirements of funding bodies and ethical gatekeepers. Engaging children and young people in consultation can offer an opportunity to refine intended data collection methods which can benefit the ethics of research, and help avoid unintended errors in study design.